The Flow and the Line: Conflict Archaeology in the Brazilian Amazon Forest - Souza, Rafael (Journal of Contemporary Archaeology, 2016)
This article reflects on the different ways in which the organizing principles and materiality of a company town—a product of control society, vigilance, and the imposition of modern notions of “civilization”—diametrically oppose Amazonian ways of occupying space and arranging landscape, using the invasion of the company town Núcleo Urbano de Carajás by members of the ethnic group Xikrin do Cateté as the starting point for discussion. I use archaeological terms to formulate a discussion about these overlapping and conflicting visions of the same territory, with the aim of constructing an alternative narrative of the Amazonian conflicts that grow alongside the expansion of great infrastructural building projects. The aim of this paper is to show the enormous toll that producing commodities to meet globalized consumerist demands has on local populations.